Scientific landscape of traditional and complementary medicine in chronic diseases in older adults: A bibliometric and qualitative analysis of the most influential literature - González-Cano, Jonathan Alexander; Mendoza-Medina, Euro Xavier; Medina-Arredondo, Sergio Alejandro; Peralta-Gamboa, Dennis Alfredo (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the scientific landscape of Traditional and Complementary Medicine (TCM) applied to chronic disease management in older adults, highlighting global research trends, thematic clusters, and collaboration networks. A mixed-methods study combining bibliometric and qualitative analyses was conducted using Scopus and Web of Science databases. Thirty-two peer-reviewed articles published between 2002 and 2025 were selected following inclusion and exclusion criteria. Data were processed using R (v4.4.2) and VOSviewer (v1.6.20) to evaluate productivity, citation impact, thematic evolution, and institutional cooperation. Results show a non-linear but sustained growth in scientific production, with peaks in 2015 and 2019 and a post-pandemic slowdown. The United States and Australia lead in productivity and impact, while Asian countries contribute emerging evidence. Three thematic clusters were identified: clinical effectiveness, emotional well-being, and complementary therapies (acupuncture, phytotherapy, meditation). TCM research on chronic diseases in older adults has achieved global relevance but remains fragmented, with limited international collaboration and a lack of standardized clinical protocols. The findings provide actionable evidence to guide public health policies, promote multicenter research, and foster integration of TCM into healthy aging programs.